DAMPAK PERUBAHAN SOSIAL TERHADAP BUDAYA GOTONG ROYONG PADA PETANI PADI DI DESA BANING PANJANG - Widiastutik, Ratna; Aminuyati, Aminuyati; Khosmas, FY. (Universitas Tanjungpura, 2022)
ABSTRACTThis study aims to determine the impact of social change on the culture of gotongroyong on rice farmers in Baning Panjang Village, Kelam Permai District,Sintang Regency. The form of research used is quantitative with associativeresearch methods, social change variables and mutual cooperation of ricefarmers. Sources of data respondents consisted of 90 rice farmers with 22questionnaire items. The results of the research on social change have anaverage of 55.10% with sufficient category. The mutual cooperation culture ofrice farmers has an average of 54.97% in the sufficient category. Based on theanalysis obtained the equation Y' = 8.589 + 0.432X with a significance value of0.000 0.05, so it can be said that Ho is rejected and HÎ± is accepted, meaningthat there is an impact of social change on the Culture of Mutual Cooperation onrice farmers in Baning Panjang Village, Kelam Permai District, SintangRegency. The magnitude of the impact obtained is 50% with sufficientcategories, that is, not high and not low and the other 50% is influenced by otherfactors outside the study.Keywords: Social Change, Mutual Cooperation Culture, Rice Farmers